First cycad seedling foliage from the fossil record and inferences for the Cenozoic evolution of cycads. (26th July 2019) - Erdei, Boglárka; Coiro, Mario; Miller, Ian; Johnson, Kirk R.; Griffith, M. Patrick; Murphy, Vickie
Abstract : The morphology of the early ontogenetic stages of cycad foliage may help resolve the relationships between extinct to extant cycad lineages. However, prior to this study, fossil evidence of cycad seedlings was not known. We describe a compression fossil of cycad eophylls with co-occurring fully developed leaves of adult specimens from the early Palaeocene ( ca 63.8 Ma) Castle Rock flora from the Denver Basin, CO, USA and assign it to the fossil genus Dioonopsis (Cycadales) based on leaf morphology and anatomy. The new fossil seedling foliage is particularly important because fully differentiated pinnate leaves of adult plants and the eophylls belong to the same species based on shared epidermal micromorphology, therefore, increasing the number of morphological characteristics that can be used to place Dioonopsis phylogenetically. Significantly, the seedling fossil has a basic foliage structure that is very similar to seedlings of extant cycads, which is consistent with a cycadalean affinity of Dioonopsis . Nevertheless, the set of morphological characters in the seedling and adult specimens of Dioonopsis suggests a distant relationship between Dioonopsis and extant Dioon . This indicates that extinct lineages of cycads were present and widespread during the early Cenozoic (Palaeogene) coupled with the subordinate role of extant genera in the Palaeogene fossil record of cycads.